(untitled) (Cadernos de Sociomuseologia, 2017)
This article aims to propose some reflections about memory, identity, territoriality and the importance of afros memorials in communities afro as a form of political strategy of a new scenic and textual language in the preservation, dissemination and re - readings of the memories projected in these spaces. Keywords: memory, identity, museum spaces.